2017
DOI: 10.1002/14651858.cd006681.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin for prevention of venous thromboembolism in patients with lower-limb immobilization

Abstract: Moderate-quality evidence showed that the use of LMWH in outpatients reduced DVT when immobilization of the lower limb was required, when compared with no prophylaxis or placebo. The quality of the evidence was reduced to moderate because of risk of selection and attrition bias in the included studies. Low-quality evidence showed no clear differences in PE between the LMWH and control groups, but less symptomatic VTE in the LMWH groups. The quality of the evidence was downgraded due to risk of bias and impreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
95
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 65 publications
6
95
1
Order By: Relevance
“…Moreover, the observation that the risk of DVT increased by 7% per each increasing year of age, is confirmed by earlier studies [1,11,20]. The finding also indicates that older age together with BMI should be considered while deciding DVT preventive interventions during leg immobilization [11,20,22]. This is the first prospective randomized study to study DVT rate during EFM.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, the observation that the risk of DVT increased by 7% per each increasing year of age, is confirmed by earlier studies [1,11,20]. The finding also indicates that older age together with BMI should be considered while deciding DVT preventive interventions during leg immobilization [11,20,22]. This is the first prospective randomized study to study DVT rate during EFM.…”
Section: Discussionsupporting
confidence: 77%
“…The finding that patients with BMI over 26 exhibited an almost threefold increased odds for sustaining a DVT at 2 weeks was supported by the literature and may reflect that specific interventions should be initiated for obese patients [20,22]. Moreover, the observation that the risk of DVT increased by 7% per each increasing year of age, is confirmed by earlier studies [1,11,20].…”
Section: Discussionsupporting
confidence: 69%
“…To what degree do symptoms need to change to suggest a risk of symptomatic VTE to both the patient and clinician? Both these issues are perhaps reflected in the highly variable incidence of VTE across the included studies, ranging from 1.8% to 40.4% . We present our outcomes in this study stratified by symptomatic disease and anatomical location of VTE to address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…The risk lingers for up to 2-3 months after surgery despite using TPX, and joint risk of death within 3 months is as high as 13% [5]. Research has shown that 4.8-40% of trauma patients who did not use TPX, developed DVT symptoms [12]. This is the reason why appropriate thromboprophylaxis in that sort of trauma is crucial, and all patients with femoral fractures should take TPX.…”
Section: Thromboprophylaxis In Particular Types Of Traumasmentioning
confidence: 99%
“…According to ACCP recommendations from 2012, prophylaxis should be applied earlier than 12 hours before surgery and 12 hours after surgery at the earliest; this is very important in acute traumas and demands for immediate surgery. Prophylaxis should last for a minimum of 10-14 days [12].…”
Section: Thromboprophylaxis In Particular Types Of Traumasmentioning
confidence: 99%